The Role of Diaspora Communities in Preserving Culture and Promoting Balinese Tourism in France - Via Oktaviani; Salwa Nabila; Sylvia Juliana Maijora (PT Syamilah Literasi Islami, 2025)
The Bali diaspora spread throughout France, driving tourism as well as Bali and Indonesia's culture. Diaspora is a term that refers to a community or ethnic group that voluntarily leaves their homeland or their ethnic origin, including spread to various places around the world, and includes the additional consequences of spread, such as genetic origin, and cultural spread. The aim of this study is to see how the Bali diaspora shapes the values, customs, and culture of Bali while preserving and introducing the Indonesian cultural identity in France as well as playing a role in enhancing tourism in Bali and Indonesia as a whole. The Bali diaspora in France is the main focus of this study, especially Paris, France, which is the most famous tourist destination in the world. This research uses a qualitative approach. Diaspora Indonesia has been able to boost Indonesian tourism in France through various activities related to the culture and art of Indonesia. The French people recognize Indonesian culture and art as the identity of their nation. It increases the nationalism of Indonesians living in France. Situations, formulas, tables, and images are not available in abstract.